PENDEKATAN PRINCIPAL COMPONENT ANALYSIS PADA DATA DEMAM BERDARAH DENGUE DI PROVINSI MALUKU UTARA - Ririhena, Seba; Loklomin, Samsul Bahri (PATTIMURA UNIVERSITY, 2020)
North Maluku Province is one of the provinces with many cases of Dengue Hemorrhagic Fever (DHF) in Eastern Indonesia. Various factors cause the increase of DHF such as environment, personal hygiene and inadequate health infrastructure in North Maluku Province The purpose of this research is to group the multivariable of dengue cases into several simpler components using the Principal Component Analysis (PCA) method. The PCA method is a statistical technique for reducing a large number of variables to become simpler. The results showed that 1 variable did not meet the KMO value so that the variable was eliminated. All variables after eliminating one of the variables are tested to meet the KMO and MSA values. All predictors in this study form 1 predictor component variable used are non-labor force population (X1), medical personnel (X2), vulnerable age population (X3), workforce population (X4), villages with health facilities (X5), health facility (X6).